2020
DOI: 10.3390/toxins12090562
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Composite Essential Oils against Aflatoxigenic Fungus Aspergillus flavus in Maize

Abstract: The efficacy of eleven essential oils (EOs) against Aspergillus flavus NRRL 3357 was investigated. The highest antifungal activity against this aflatoxigenic fungus was exhibited by cinnamon, oregano and lemongrass, which showed low minimum inhibitory concentration (MIC) values under vapor conditions. Interactions of the three EOs were evaluated by the fractional inhibition concentration index (FICI), and the composite essential oils (CEO) showed synergistic inhibitory activities. Chemical analysis of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 72 publications
(80 reference statements)
4
21
1
Order By: Relevance
“…Although the majority of studies used FIC analyses to assess antibacterial combinations of EOCs, very few and recent studies also addressed antifungal FIC analyses. The combination of cinnamon and lemongrass showed synergistic effects (FIC = 0.75) for Aspergillus flavus [ 51 ], which is lower than our FICs for A. niger ( Table 2 ). Another study showed that the combination of cinnamaldehyde and citral was effective against Penicillium expansum and caused membrane damages, including a loss of membrane integrity and ergosterol content [ 52 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Although the majority of studies used FIC analyses to assess antibacterial combinations of EOCs, very few and recent studies also addressed antifungal FIC analyses. The combination of cinnamon and lemongrass showed synergistic effects (FIC = 0.75) for Aspergillus flavus [ 51 ], which is lower than our FICs for A. niger ( Table 2 ). Another study showed that the combination of cinnamaldehyde and citral was effective against Penicillium expansum and caused membrane damages, including a loss of membrane integrity and ergosterol content [ 52 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The MIC value of CLCEO against strain YQM was 0.0313 µL/mL, which indicated the CLCEO had a good antifungal effect on strain YQM. Based on the criterion [ 26 ], the FIC index was 0.28, indicating that the antifungal effect of different kinds of EOs was synergistic. Consequently, it could be concluded that CEO and LEO had a synergistic interaction on inhibiting the growth of strain YQM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the antifungal effect of combined EOs is better than that of single EOs by combining two or more EOs to create a synergistic effect [ 38 ]. For example, Xiang et al [ 26 ] found that there was a synergistic antifungal effect among cinnamon, oregano, and lemongrass EOs, and the composite EO consisting of three EOs with the volume ratio of 1:5:48 displayed remarkable inhibitory activity against the mycelial growth of A . flavus and aflatoxin production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus niger has been considered a contributor to aspergillosis lung disease; however, aspergillosis is most frequently caused by the co-occurrence of more toxic species of Aspergillus genera, with Aspergillus fumigatus being the primary cause [ 17 ]. The second most common cause of aspergillosis lung disease is Aspergillus flavus , a primary producer of a wide variety of mycotoxins, including the highly carcinogenic aflatoxins [ 18 ]. The most important mycotoxins produced by Penicillium species include ochratoxins and patulin [ 19 ].…”
Section: Introductionmentioning
confidence: 99%